1999
DOI: 10.1161/01.atv.19.10.2340
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Angiogenic Protein, Platelet-Derived Endothelial Cell Growth Factor, in Coronary Atherosclerotic Plaques

Abstract: Abstract-Recent information indicates that platelet-derived endothelial cell growth factor (PD-ECGF), a 45-kDa angiogenic protein, is expressed in the endothelium of various tissues and that its level of expression is correlated with the number of microvessels in human tumors. Because the formation of neovessels is also thought to play a role in atherosclerotic vascular remodeling, we analyzed PD-ECGF expression in fresh, coronary plaque tissues obtained by directional coronary atherectomy. Specimens from 31 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 38 publications
3
19
0
1
Order By: Relevance
“…Although preferentially expressed by cancer cells, TP is also present in normal tissues, including the endothelium (Fox et al, 1995;Schüller et al, 2000). Furthermore, TP (also known as platelet-derived endothelial cell growth factor) has been demonstrated in coronary atherosclerotic plaques where it may play a pathogenetic role (Ignatescu et al, 1999). Based on our results, we propose that 5FU induces TP in endothelial cells and thus sustains its own activation.…”
Section: Figuresupporting
confidence: 60%
“…Although preferentially expressed by cancer cells, TP is also present in normal tissues, including the endothelium (Fox et al, 1995;Schüller et al, 2000). Furthermore, TP (also known as platelet-derived endothelial cell growth factor) has been demonstrated in coronary atherosclerotic plaques where it may play a pathogenetic role (Ignatescu et al, 1999). Based on our results, we propose that 5FU induces TP in endothelial cells and thus sustains its own activation.…”
Section: Figuresupporting
confidence: 60%
“…It has been reported that intratumoral macrophages express TP in human malignancies 14,15,[17][18][19] and that activated mast cells express TP in atherosclerotic plaques. 25 Activated mast cells also express VEGF 27 and bFGF. 34 Distinct patterns of TP expression have been observed in human malignancies of various organs.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that TP expression has been correlated with the number of microvessels and mast cells in coronary atherosclerotic plaques. 25 Angiogenic factors, including TP, stimulate mast cell migration in vitro. 26 Recent investigations [27][28][29] have demonstrated that mast cell accumulation is associated with tumor angiogenesis and poor outcome in patients with NSCLC, and especially in patients with adenocarcinoma of the lung.…”
mentioning
confidence: 99%
“…[25][26][27][28] dRib is in fact a relevant source for in vivo oxidative stress 29,30 being synthesised by thymidine phosphorylase, an enzyme whose expression is induced by hypoxia and chronic inflammation, two conditions that share in the pathogenesis of atherosclerosis and its complications. 31, 32 Since we noted that the difference in in vitro apoptosis susceptibility of the p53 codon 72 genotypes was evident predominately in old people (sexagenarians and centenarians), we investigated the in vivo relevance of the phenomenon in old subjects. Purposely, we correlated p53 codon 72 genotype with serum Troponin I and CK-MB levels (which are specific quantitative markers for the extent of the ischaemic injury) in a group of aged patients (65-99 years of age) affected by acute coronary syndrome (ACS), a clinically relevant condition determined by ischaemic cell death of the myocardial tissue.…”
Section: Introductionmentioning
confidence: 99%